Analisis makna metafora dalam syair burdah imam al-bushiri - rochma, siti seinur (Maliki Interdisciplinary Journal, 2025)
This research analyzes the meaning of metaphor in the burdah poem by imam al-bushiri, a famous Muslim poet in the 13th century AD. The purpose of this research is to analyze and reveal the meaning and messages contained in al-bushiri’s burdah poem. The research method used in the study is a qualitative approach with the type of critical discourse analysis to examine the meaning of metaphors in Imam al-Bushiri’s Syair Burdah. The research method used is descriptive analytical method which aims to describe and analyze in depth the meaning of metaphors in the poem text. The results of this study the author found 8 stanzas of data in the chapter في التحذير من هوى النفس (Warning of the Dangers of Lust) which included metaphorical expressions in the burdah of al-bushiri. It was found that there are 6 data using structural metaphors, and 2 other data using ontological metaphors, and no data found using orientational metaphors. In conclusion, this study contributes to understanding and interpreting the meaning of metaphors in Imam al-Bushiri’s Burdah poem. This kind of research is important to preserve literary heritage and explore the spiritual messages contained in works of Islamic literature.